Pembentukan Karakter Mandiri Melalui Kokurikuler Keterampilan Khusus dalam Kurikulum Merdeka: Studi Kasus di SD Ar-Rahman Kertosono Nganjuk - Moh. Rizal Afandi; Marita Lailia Rahman; Badrus Badrus (STIKes Ibnu Sina Ajibarang, 2025)
Character education has become the focus of various countries in order to prepare a quality generation. Various problems arise with the development of modern technology in society. One of them is moral decline or what we often call moral degradation. The formation of character values ​​can be taught to students not only in the form of activities in class but also through activities outside the classroom or what is called co-curricular learning. The aim of this research is to describe and analyze the independent curriculum co-curricular program at SD Ar-Rahman Kertosono as an effort to build independent character in students. This research is qualitative research with a case study type of research. Data collection techniques use interviews, observation and documentation. Meanwhile, for data analysis, researchers carried out data reduction, data presentation, and drawing conclusions. This research produces findings that in the process students need to go through several character formation processes including moral knowledge, moral feelings and moral actions. These three processes are included in co-curricular activities at SD Ar-Rahman Kertosono.